Regulation of circGOLPH3 and its binding protein CBX7 on the proliferation and apoptosis of prostate cancer cells. Issue 12 (23rd December 2020) - Gong, Lifeng; Tang, Yu; Jiang, Li; Tang, Wei; Luo, Shengjun
Abstract: To clarify the mechanism of circGOLPH3 regulation on prostate cancer cells, we performed an overexpression and interference circGOLPH3 assay in prostate cancer cells PC-3 and then evaluated cellular viability, proliferation, cell cycle, and apoptosis of prostate cancer cells by MTT, CCK8, Edu stain, TUNEL stain, and flow cytometry. Binding proteins of CircGOLPH3 were identified by RNA pull-down, mass spectrometry, and RNA-binding protein immunoprecipitation (RIP) assays. The expressions of CircGOLPH3 and CBX7 were measured by qRT-PCR. The results showed that after overexpression of circGOLPH3, the proliferative capacity and the viability of PC-3cells were significantly improved, whereas apoptosis was inhibited. CircGOLPH3 could bind to the CBX7 protein that was highly expressed in the PC-3 cell. Additionally, a functional test on CBX7 showed that the CBX7 overexpression notably improved the proliferative capacity and the viability of PC-3 cells and decreased cellular apoptosis, which was consistent with the effects of circGOLPH3. The validated the present study that circGOLPH3 and its binding protein CBX7 can promote prostate cancer cell proliferation and inhibit apoptosis.